Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kepuasan Kerja Pegawai Bappeda Kabupaten Jeneponto - Sewang Sewang (Public Service and Governance Journal, 2023)
This study aims to analyze the effect of organizational culture and leadership style on the job satisfaction of Bappeda Jeneponto Regency employees. The location of this research is the Office of the Regional Development Planning Agency (Bappeda). The sample in this study used the census method (saturated sample) with a total of 32 respondents. Data collection was done through questionnaires with the analysis method was multiple linear regression analysis. The results showed that organizational culture had a positive and significant effect on the job satisfaction of Jeneponto Regency Bappeda employees with a coefficient of determination of 0.377 and P (sig) = 0.000 < 0.05. This shows that the better the organizational culture and understanding by employees, the better job satisfaction will be. Leadership style has a positive and significant effect on the job satisfaction of Bappeda Jeneponto Regency employees with a determination coefficient value of 0.548 and P (sig) = 0.000 <0.05. This shows that the better the leadership style, the better job satisfaction will be. The variable that has a dominant effect on the job satisfaction of Bappeda Jeneponto Regency employees is leadership style.